ANALISIS KEPUTUSAN PEMBELIAN PADA SAAT PANDEMI COVID-19 DI TOKO BIBIT TANAMAN DAN BUAH JUWET LESTARI - Safitri, Dina; Zulistiani, Zulistiani; Yudho L, Poniran (Universitas Nusantara PGRI Kediri, 2022)
Analyzing and knowing the significant effect of product quality, price and promotion on purchasing decisions during the Covid-19 pandemic (Case Study at the Juwet Lestari Fruit and Plant Seed Shop) is a goal that will be achieved by researchers. Quantitative is the approach, with the technique being causal. The sample is 40 respondents, with the technique of taking it using accidental sampling. The data analysis technique uses multiple linear regression analysis with the help of SPSS software for windows version 23. The conclusions of this study are that there is a partial and simultaneous effect of product quality, price and promotion on purchasing decisions during the Covid-19 pandemic (Case Study at the Juwet Plant Seed and Fruit Store). sustainable).